(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
Notes on psychotropic drugs, where they work and their potentially therapeutic use or abuse for social control. Psychotropic drugs and the ability to communicate and interact: a pathological simplification. Interference on communication on an emotional level, but also on the use of languages. The complex problem of the translator/mediator with concrete examples. Observations on CPRs as total institutions in the sense of Goffmann. Physical, emotional, cultural distances and the interference of drugs. A parallel discussion should be made on the experiences, both of guests and those who work there. Intercultural identity: a problem or an asset. Ideological obstacles to welcoming, without care there is no freedom.